Numerical and experimental investigation on topology optimization of an elongated dynamic system. (15th February 2022) - Lopes, Heitor Nigro; Cunha, Daniel Candeloro; Pavanello, Renato; Mahfoud, Jarir
Abstract: Minimizing vibration levels of dynamic components at their operating frequency range has been a widely studied topic in engineering. However, the design of structures that satisfy geometric constraints and technical performances is an ongoing challenge. In this work, a topology optimization procedure based on the Bi-directional Evolutionary Structural Optimization (BESO) algorithm is performed to maximize the natural frequency separation interval of an elongated structure. The issues of disconnected and trivial solutions are solved using a connectivity constraint. It is imposed by a proposed procedure based on the heat flux solution of an auxiliary system. An assessment of the feasibility of the structure is done by verifying its accordance with manufacturing and design constraints. The optimized structure was manufactured and validated experimentally. The implemented process produces topologies that maximize the natural frequency separation and reduce the mass of the structure. The obtained results demonstrate the effectiveness of the proposed procedure at satisfying geometric design constraints and technical performances.